Comparison of two serpins of Clonorchis sinensis by bioinformatics, expression, and localization in metacercaria. (June 2014) - Yang, Yabo; Hu, Dong; Wang, Lexun; Liang, Chi; Hu, Xuchu; Xu, Jin; Huang, Yan; Yu, Xinbing
Abstract : Clonorchiasis, which has been an important public health problem in China, is caused by ingestion of raw or undercooked fish contaminated by live metacercaria. Therefore, preventing fish from infecting is of great significance for controlling the disease. SERPINs (serine protease inhibitors) are well known as negative regulators of hemostasis, thrombolysis, and innate immune responses. In the present study, two full-length sequences encoding SERPIN were identified from metacercaria cDNA library of Clonorchis sinensis ( C. sinensis ) and were denominated as Cs SERPIN and Cs SERPIN3, respectively. Bioinformatics analysis showed that the two sequences shares 35·9% identity to each other. Both of the sequences have SERPIN domain and the greatest difference between the two domains is the reactive centre loop. Transmembrane region was found in Cs SERPIN3 while not in Cs SERPIN. The expression of the two Cs SERPINs was significantly higher at the life stage of metacercaria than that of adult. The transcription levels of Cs SERPIN and Cs SERPIN3 at metacercaria stage were 3·249- and 11·314-fold of that at adult stage, respectively. Furthermore, the expression of Cs SERPIN was 4·32-fold of that of Cs SERPIN3 at metacercaria stage. Immunobiochemistry revealed that Cs ERPIN was dispersed at subtegument and oral sucker of metacercaria, while Cs SERPIN3 localized intensely in the tegument of metacercaria of C. sinensis inside of the cyst wall. All these indicated that the Cs SERPINs play important roles at metacercaria stage of the parasite. Cs SERPIN may take part in regulation of endogenous serine proteinase and Cs SERPIN3 may be involved in immune evasion and be a potential candidate for vaccine and drug target for clonorchiasis.